Interaksi Eksekutif-Birokrasi di Kota Bandar Lampung = Executive-Bureaucracy Nexus in Bandar Larnpung District - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
This project seeks: (a) to describe the .pattern of nexus executives-bureaucracy in Bandar Lampung municipality